Polycystic ovary syndrome: clinical and laboratory evaluation - Khoury, Marcos Yorghi; Baracat, Edmund Chada; Pardini, Dolores Perovano; Haidar, Mauro Abi; Motta, Eduardo Leme Alves da; Lima, Geraldo Rodrigues de (São Paulo Medical Journal, 1996)
OBJECTIVE: To evaluate clinically, and with laboratory, tests, women with polycystic ovary syndrome (PCO). PATIENTS: One hundred and twelve women with PCO were studied. METHODS: The following data was recorded: Current age; age at menarche; menstrual irregularity, occurrence of similar cases in the family; fertility, obstetric history; body mass index (BMI); and presence of hirsutism. Serum measurements of follicle stimulating hormone (FSH), luteinizing hormone (LH), prolactin, free testosterone, and dehydroepiandrosterone sulfate were taken. RESULTS: All patients presented either oligomenorrhea (31 percent), periods of secondary amenorrhea (9 percent), or both alterations (60 percent). The majority of the patients were infertile (75.6 percent). The LH/FSH ratio was higher than 2:1 in 55 percent of the patients and higher than 3:1 in 26.2 percent. The ultrasonographic aspect of the ovaries was considered to be normal in 31 percent. CONCLUSION: The main clinical feature of the PCO is the irregularity of menses since menarche, and that the laboratory tests would be important to exclude other disorders such as hyperprolactinemia or hyperandrogenemia caused by late-onset congenital adrenal hyperplasia.